Voltammetric determination of dipyrone using a N,N′- ethylenebis(salicylideneaminato)oxovanadium(IV) modified carbon-paste electrode - Teixeira, Marcos F. S. [UNESP]; Marcolino-Júnior, Luiz H.; Fatibello-Filho, Orlando; Dockal, Edward R.; Cavalheiro, Éder T. G. (My University, 2004)
The preparation and electrochemical characterization of a carbon paste electrode modified with N.N′-ethylenebis(salicylideneiminato) oxovanadium(IV) complex ([VO(Salen)]) as well as its behavior as electrocatalyst toward the oxidation of dipyrone were investigated. The electrochemical behavior of the modified electrode and the electrooxidation of dipyrone were explored using cyclic voltammetry. The voltammetric response of the modified electrode is based on two reactions. One electrochemical related to the oxidation of the metallic center of the [VO(Salen)] and the other involving the chemical redox process involving the oxidized form of the complex and the reduced form of dipyrone. The best voltammetric response was observed for a paste composition of 25% (m/m) [VO(Salen)], KCl solution pH from 5.5 to 8.0 as the electrolyte and potential scan rate of 10 mV s-1 in the presence of dipyrone. A linear voltammetric response for dipyrone was obtained in the concentration range from 9.9 × 106 to 2.8 × 10 -3 mol L-1, with a detection limit of 7.2 × 10 -6 mol L-1. Among of several compounds tested as potential interference, only ascorbic acid presented some interference. The proposed electrode is useful for the quality control and routine analysis of dipyrone in pharmaceutical formulations.
Keywords: Dipyrone; Modified electrode; N,N′-ethylenebis(salicylideneiminato)oxovanadium(IV); Pharmaceutical formulations; Voltammetric determination; ascorbic acid; carbon; dipyrone; electrolyte; n,n' ethylenebis(salicylideneaminato)oxovanadium; potassium chloride; unclassified drug; vanadium derivative; acidity; alkalinity; chemical composition; complex formation; concentration process; cyclic potentiometry; electrochemistry; electrode; linear system; oxidation; oxidation kinetics; oxidation reduction reaction; paste; pharmaceutical engineering